Peers are the measure of all things: moderating and mediating the association between victimization and depressed affect among Brazilian adolescents - Santo, Jonathan B.; da Cunha, Josafá M. (Frontiers in Developmental Psychology, 2026)
IntroductionInternalizing symptoms in general and depression in particular is a significant health concern among adolescents, with peer victimization as a consistent risk factor. The current study aimed to examine the association between peer victimization and depressed affect among Brazilian adolescents, as well as the potential buffering effect of close friends and the indirect effect of social support on this association.MethodsData were analyzed from the PeNSE National Survey of School Health, a nationally representative sample of 5th to 11th grade Brazilian students (final N = 154,122). Participants completed self-administered questionnaires assessing peer victimization, number of friends, social support, and internalizing symptoms.ResultsPeer victimization was found to be a significant predictor of depressed affect, and reporting more close friends was related to lower depressive symptoms. The study also found evidence for a curvilinear relationship between the number of close friends and depressed affect. More importantly, the number of close friends buffered the effect of peer victimization whereas peer support mediated the association to depressed affect.DiscussionThese findings highlight the importance of addressing both peer victimization and social support in promoting mental health among Brazilian adolescents in addition to making the school environment less challenging for all students.